Rental Housing : Lessons from International Experience and Policies for Emerging Markets - Peppercorn, Ira Gary; Taffin, Claude (Washington, DC: World Bank, 2013)
This book rental housing lessons from international experience and policies for emerging market is an effort to bring rental housing to the forefront of the housing agenda of countries around the world and to provide general guidance for policy makers whose actions can have an effect on where and how people live. It warns of the challenges they face and provides guidelines on how to develop or redevelop a sound rental sector. it can enable key players in housing markets be they government officials, private rental property owners, financiers, or nongovernmental organizations to add rental housing as a critical housing option and to have an informed discussion on how best to stimulate this sector. The housing policy of most nations focused on increasing home ownership. There had been very little discussion about rental housing, less about social housing, and virtually none about public housing. This book includes totally five chapters: chapter one is introduction; chapter two is the rental market and its players; chapter three is legal, tax, and financial issues; chapter four is recommendations and conclusion; chapter five is country experiences.